2012
DOI: 10.1007/s11897-012-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Cardiotoxicity

Abstract: Anthracycline-based chemotherapeutics have long been recognized as effective agents for treating a wide range of malignancies. However, their use is not without significant adverse cardiotoxic side effects. Strategies for prevention involve limiting free-radical production and subsequent cardiac myocyte damage. Dexrazoxane remains the most widely studied cardioprotective medication. Alternative agents may reduce cardiotoxicity but may still cause significant cardiovascular problems. The role of β-blockers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…Binding of Doxorubicin with the cell results in the production of active oxygen species, especially hydroxyl radicals. This leads to a decline of mitochondrial oxidative phosphorylation [1,6,7]. Administering Doxorubicin via intravenous injections leads to several side effects associated with chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of Doxorubicin with the cell results in the production of active oxygen species, especially hydroxyl radicals. This leads to a decline of mitochondrial oxidative phosphorylation [1,6,7]. Administering Doxorubicin via intravenous injections leads to several side effects associated with chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The induced cardiotoxicity can be acute, usually manifesting within the first 2–3 days of administration. Doxorubicin cardiomyopathy once developed has poor prognosis and is frequently fatal, affecting nearly 11% of all patients [7,8]. In order to overcome systemic toxicity caused by drug administration, Doxorubicin can be administered instead as a molecular theranostic agent with targeted delivery to Scavenger receptors type B1 (SR-B1) overexpressed in tumors; by encapsulation in reconstituted high density lipoprotein (rHDL) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, targeting the ubiquitin‐proteasome pathway is an emerging concept in cancer therapy based on the hypothesis that many proteins in the proteasome are implicated in the regulation of important processes of carcinogenesis and cancer cell survival . Several proteasome‐targeting inhibitors (e.g., bortezomib, carfilzomib) have been introduced in the clinic. A retrospective analysis of 3954 patients in phase 2/3 trials of bortezomib for the treatment of multiple myeloma reported that bortezomib‐based treatment was associated with a low incidence of cardiac events .…”
Section: Fda‐approved Mtts For Oncologymentioning
confidence: 99%
“…Modern therapeutic approaches against advanced stage solid tumors include chemotherapy or radiotherapy, which are found to be very much detrimental to the host due to their non-specific action. [1][2][3] Moreover, most of the advanced stage solid tumors often metastasize from their site of origin to distant organs, thereby adding further complication to their treatment. 4 In this regard, immunotherapeutic approaches may be helpful due to their specific action on cancer cells.…”
Section: Introductionmentioning
confidence: 99%